Multiple Cranial Neuropathies Similar to Orbital Apex Syndrome Associated with Pembrolizumab: A Case Report - Taku Nishimura; Toshio Sakatani; Hideyuki Takeshima; Shunichi Matsuda; Toshihiro Yoshizawa; Kazuhiro Usui (Case Reports in Oncology, 2022)
Neurotoxicity is one of the more serious immune-related adverse events (irAEs) linked to immune checkpoint inhibitors and calls for prompt diagnosis and treatment. We describe a case of posttreatment anti-programmed death-1 immune checkpoint inhibitor pembrolizumab-induced oculomotor, optic, and trigeminal neuropathy in an 84-year-old female patient with recurrent pulmonary adenocarcinoma. After she received 13 cycles of pembrolizumab, she experienced hyponatremia, anorexia, and right ptosis. There were signs of the suspected irAEs of pembrolizumab, including trigeminal neuropathy, optic neuropathy, and oculomotor neuropathy. Steroid pulse therapy had good results for her neurological findings. We reported this case despite reports of pembrolizumab-induced mononeuropathy of the oculomotor and optic nerves because multiple cranial neuropathies like orbital apex syndrome are thought to be uncommon.